SEPARATION AND ELEMENTATION OF DIMER STILBENOID STRUCTURE OF VATICA LIGHT STEEL UMBONATA BURCK (DIPTEROCARPACEAE) - Sri Atun (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2007)
Three oligostilbenoid, namely (-)-ampelopsin F (1), laevifonol (2), ande-viniferin (3) had been isolated and elucidated these structure from the stem bark of Vatica umbonata Burck (Dipterocarpaceae). The structure of three compounds were elucidated based on physical and spectroscopic data UV,JR, IH and HCNMR, HMBC, HMQC, COSY, andNOESY.